2011
DOI: 10.1007/s12079-011-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

CCN3-mediated promotion of sulfated proteoglycan synthesis in rat chondrocytes from developing joint heads

Abstract: Chondrocytes forming articular cartilage are embedded in a vast amount of extracellular matrix having physical stiffness and elasticity, properties that support the mechanical load from bones and enable the flexible movement of synovial joints. Unlike chondrocytes that conduct the growth of long bones by forming the growth plate, articular chondrocytes show suppressed cell proliferation, unless these cells are exposed to pathological conditions such as mechanical overload. In the present study, we found that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The ECM of the articular cartilage in Nov del3 −/− male mice was also significantly different at 6 months, with decreased levels of proteoglycans and increased collagen fibre thickness compared to age and sex-matched littermates. Consistent with this, NOV has been reported to promote sulphated proteoglycan synthesis in chondrocytes isolated from developing rat epiphysis 24 . It would be of interest to determine whether ECM proteins that regulate collagen fibril size and diameter, such as decorin and collagen IX are altered in the Nov del3 −/−mice.…”
Section: Discussionsupporting
confidence: 65%
“…The ECM of the articular cartilage in Nov del3 −/− male mice was also significantly different at 6 months, with decreased levels of proteoglycans and increased collagen fibre thickness compared to age and sex-matched littermates. Consistent with this, NOV has been reported to promote sulphated proteoglycan synthesis in chondrocytes isolated from developing rat epiphysis 24 . It would be of interest to determine whether ECM proteins that regulate collagen fibril size and diameter, such as decorin and collagen IX are altered in the Nov del3 −/−mice.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, application of MIA to articular cartilage in vivo results in immediate expenditure of CCN3 in articular cartilage and production of CCN3 in clustering chondrocytes, suggesting its role in cartilage protection (Janune et al 2017). CCN3 is shown to maintain the differentiated phenotype of articular chondrocytes, repressing their proliferation to save energy consumption (Janune et al 2011). Therefore, this metabolic regulation of CCN3 may be of critical significance in the maintenance of articular cartilage, although its precise molecular mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…OA, a major clinical problem among the ageing population, is characterized by articular cartilage degeneration and synovial inflammation. CCN3 was highly expressed in articular chondrocytes in the normal rat articular cartilage [ 17 ], but it has an apparent decline in a monoiodoacetic acid- (MIA-) induced osteoarthritic model [ 56 ]. Consistently, another research also confirmed that the CCN3 expression was reduced in the cartilage tissue of OA patients and OA rat models [ 57 ].…”
Section: The Roles Of Ccn3 Protein In Immune-related Diseasesmentioning
confidence: 99%
“…In human early embryonic development, CCN3 is widely expressed in the derivative of all three germ layers [ 15 ]. In adult mammals, high CCN3 expression is observed in endotheliocytes, smooth muscle cells, fibroblasts, and chondrocytes [ 14 , 16 , 17 ]. Besides, Dombrowski et al first discovered that CCN3 can be produced by regulatory T cells (Treg) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%